Chondroitinase ABC Administration Facilitates Serotonergic Innervation of Motoneurons in Rats With Complete Spinal Cord Transection - Takiguchi, Masahito; Miyashita, Kanae; Yamazaki, Kohei; Funakoshi, Kengo (Frontiers in Integrative Neuroscience, 2022)
Chondroitinase ABC (ChABC) is an enzyme that degrades glycosaminoglycan side-chains of chondroitin sulfate (CS-GAG) from the chondroitin sulfate proteoglycan (CSPG) core protein. Previous studies demonstrated that the administration of ChABC after spinal cord injury promotes nerve regeneration by removing CS-GAGs from the lesion site and promotes the plasticity of spinal neurons by removing CS-GAGs from the perineuronal nets (PNNs). These effects of ChABC might enhance the regeneration and sprouting of descending axons, leading to the recovery of motor function. Anatomical evidence, indicating that the regenerated axons innervate spinal motoneurons caudal to the lesion site, however, has been lacking. In the present study, we investigated whether descending axons pass through the lesion site and innervate the lumbar motoneurons after ChABC administration in rats with complete spinal cord transection (CST) at the thoracic level. At 3 weeks after CST, 5-hydroxytryptamine (5-HT) fibers were observed to enter the lesion in ChABC-treated rats, but not saline-treated rats. In addition, 92% of motoneurons in the ventral horn of the fifth lumbar segment (L5) in saline-treated rats, and 38% of those in ChABC-treated rats were surrounded by chondroitin sulfate-A (CS-A) positive structures. At 8 weeks after CST, many 5-HT fibers were observed in the ventral horn of the L5, where they terminated in the motoneurons in ChABC-treated rats, but not in saline-treated rats. In total, 54% of motoneurons in the L5 ventral horn in saline-treated rats and 39% of those in ChABC-treated rats were surrounded by CS-A-positive structures. ChABC-treated rats had a Basso, Beattie, and Bresnahan (BBB) motor score of 3.8 at 2 weeks, 7.1 at 3 weeks, and 10.3 at 8 weeks after CST. These observations suggest that ChABC administration to the lesion site immediately after CST may promote the regeneration of descending 5-HT axons through the lesion site and their termination on motoneurons at the level of caudal to the lesion site. ChABC administration might facilitate reinnervation by degrading CS-GAGs around motoneurons. Motor function of the lower limbs was significantly improved in ChABC-treated rats even before the 5-HT axons terminated on the motoneurons, suggesting that other mechanisms may also contribute to the motor function recovery.